Evaluation of Medication Errors detected in Private Health Sector prescriptions in Asuncion, Paraguay. - Rotela de Grau, Virginia (2020)
The aim of the present research, performed in the National University of Asuncion, is to determine the prevalence of Medication Errors in prescription orders at the Private Health Sector Pharmacy in Paraguay. Methods: This is a retrospective observational study, whose main variable was the error in prescriptions, and its secondary variables were the number of patients reached by the errors and the type of error detected. A simple random sampling technique was used to obtain 670 cases among the universe of prescriptions made during the study period. Prescription errors were grouped according to the type of errors found. Results: 56.2% of the prescriptions received at the Pharmacy sector have between 1 to 5 errors, and only in 43.8% of the cases, the prescriptions were complete. The most prevalent error was the omission of the patient's name, representing 51.58% of the total errors. The second most frequent type of error was the omission of the date of the prescription (20.18%), followed by errors in the pharmaceutical form (either by omission or by error) with 8.42%. Other types of errors represent percentages less than 8%. The prevalence of prescription of medications by their generic name reached only 0.14 of the total prescriptions evaluated. Conclusion: In-depth training of prescribers of the Private Health Sector in Paraguay is necessary. Encouraging the development of technical skills in conjunction with active pharmaceutical care could improve the quality of the prescription and reduce the amount of medical errors in the Paraguayan private health sector.